The Practice of Patronage in Elections And Its Implications for Democratic Credibility in Indonesia - Handoko, Priyo; Rohmah, Elva Imeldatur; Farida, Anis (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2023)
Patronage in Indonesian elections often occurs, especially among political elites and legislative candidates. It may be due to the need for candidates to gain votes and support from the public, and the practice of patronage is considered effective in achieving this goal. The study aims to identify voter patronage practices and measure the impact of patronage practices on the credibility of democracy in Indonesia. This research is qualitative, and data is obtained through document analysis and related literature. Election patronage practices can take many forms, ranging from money or goods to voters, unrealistic political promises, to employing positions or powers to influence voter decisions. The study found that patronage practices can significantly impact the credibility of democracies, thus disrupting democratic processes and affecting the quality of elections in Indonesia. The approach can undermine democratic principles that are supposed to be based on free and fair participation and competitive competition based on political ideas and visions. When elections were influenced by material benefits rather than political views, the public felt that elections no longer represented their aspirations and interests, resulting in dubious legitimacy over the elected government. Therefore, efforts are needed to combat patronage practices in general elections in Indonesia. This can be done through implementing strict regulations related to campaign funding and political practices, education and political literacy for the public, strict law enforcement for patronage practices, and improving the general election system to make it more transparent and accountable